1965
DOI: 10.1037/h0022525
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy of recognizing American and international road signs.

Abstract: This study investigated the hypothesis that symbol road signs (similar to the international signs) could be more accurately recognized than word road signs (typical of the American signs). The Ss used were 81 college undergraduates. The hypothesis was significantly supported under 2 conditions. Under 1 condition, both the symbols and signs were black; in the other, the symbols were black and red. A further phase of the study demonstrated the ease with which the symbol signs were learned A simple memory test co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 1 publication
1
30
0
Order By: Relevance
“…Pellegrino, Rosinski, Chiesi, and Siegel (1977) reported that when two objects belong to the same category, pictures depicting them are processed faster than words. Information is also conveyed more directly through the use of images; pictorial road signs are understood easily and accurately and are learned more easily than word signs (Walker, Nicolay, & Stearns, 1965). There is also strong evidence that symbols and icons are more easily identified and better remembered.…”
mentioning
confidence: 95%
“…Pellegrino, Rosinski, Chiesi, and Siegel (1977) reported that when two objects belong to the same category, pictures depicting them are processed faster than words. Information is also conveyed more directly through the use of images; pictorial road signs are understood easily and accurately and are learned more easily than word signs (Walker, Nicolay, & Stearns, 1965). There is also strong evidence that symbols and icons are more easily identified and better remembered.…”
mentioning
confidence: 95%
“…One of the most common methods is simply to ask people to write down a brief definition of the meaning of a sign (Brainard et al, 1961;Walker et al, 1965;Cahill, 1975;Easterby and Zwaga, 1976;Collins and Lerner, 1982). In addition to indicating the understandability of the symbol, wrong answers from the definition procedure provide insight into the kinds of confusions and misunderstanding associated with a particular symbol.…”
Section: Methods Of Evaluationmentioning
confidence: 99%
“…For example, Walker et al [4] stated that symbols and signs are more easily interpreted and learned, because of their greater perceptual simplicity. Rogers and Osborne [5] found that people tend to crystallise abstract concepts in terms of concrete symbols that can be visually represented.…”
Section: Advantages Of Visual Representationsmentioning
confidence: 99%